Temperature Exposure and Acute Cardiovascular Disease Risk in New York City: Case Time Series - Helena Krasnov; Kiran P. Nagdeo; Pablo Knobel; Elena Colicino; Allan Just; Michael Hadley; Maayan Yitshak‐Sade (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Numerous studies investigated the associations between myocardial infarction (MI), ischemic stroke, and temperature exposure, but the results vary widely, particularly in dense metropolitan areas. Methods We included all patients admitted to Mount Sinai hospitals with MI or ischemic stroke (2011–2019). We obtained daily mean, minimal, maximal, and diurnal temperature range (DTR) exposures from geospatial models. We used distributed lag nonlinear models in a case time series design to study the cumulative associations of each outcome with exposure to the different temperature metrics at lag days 0 to 6. Results We included 8933 individuals. We found cumulative higher odds of ischemic stroke associated with higher mean (odds ratio [OR], 1.010 [95% CI, 1.004–1.016]); maximal (OR, 1.010 [95% CI, 1.004–1.015]) and minimal temperatures (OR, 1.011 [95% CI, 1.004–1.017]) on 0 to 6 days before the event. We observed a nonlinear association between DTR and MI. Comparing exposure at the 10th percentile of DTR (3.8 °C) to the median (8 °C), we observed an OR of 1.332 (95% CI, 1.164–1.528), with similar effect estimates across lags. The OR of MI among those exposed to 12 °C (the 90th percentile of DTR) compared with the median was 1.041 (95% CI, 0.932–1.163). Conclusions We found higher odds of ischemic stroke associated with increased temperature exposures, highlighting the potential stroke risks in a warming climate. Additionally, we found higher odds of MI associated with lower DTR, a pattern more common on colder days. This suggests DTR may capture cardiac effects not observed using traditional exposure metrics.